Molecular mechanism and potential therapeutic targets of liver metastasis from gastric cancer - Li, Difeng; Zhang, Xin; Jiang, Lili (Frontiers in Oncology, 2022)
Gastric cancer (GC) is characterized by high invasion and poor prognosis. The occurrence of liver metastasis seriously affects advanced GC prognosis. In recent years, great progress has been made in the field of GC liver metastasis. The abnormal expression of related genes leads to the occurrence of GC liver metastasis through metastasis cascades. The changes in the liver microenvironment provide a pre-metastasis condition for GC cells to colonize and grow. The development of several potential therapeutic targets might provide new therapeutic strategies for its treatment. Therefore, we reviewed the regulatory mechanism of abnormal genes mediating liver metastasis, the effect of liver resident cells on liver metastasis, and potential therapeutic targets, hoping to provide a novel therapeutic option to improve the quality of life and prognosis of GC patients with liver metastasis.